A randomised crossover trial of minimising medical terminology in secondary care correspondence in patients with chronic health conditions: impact on understanding and patient reported outcomes. Issue 5 (May 2016) - Wernick, M.; Hale, P.; Anticich, N.; Busch, S.; Merriman, L.; King, B.; Pegg, T.
Abstract : Background: There is little existing research on the role that secondary care letters have in ensuring patient understanding of chronic health conditions. Aim: To determine whether minimising the use of medical terminology in medical correspondence improved patient understanding and anxiety/depression scores. Methods: A single‐centre, non‐blinded, randomised crossover design assessed health literacy, EQ‐5D scores and the impact of the 'translated' letter on the doctor's professionalism, the patient's relationship with their general practitioner (GP) and their perceived impact on chronic disease management. Patients were crossed over between their 'translated' and original letter. Results: Sixty patients were recruited. Use of a 'translated' letter reduced mean terms not understood from 7.78 to 1.76 ( t (58) = 4.706, P < 0.001). Most patients (78.0%) preferred the 'translated' letter, with 69.5% patients perceiving an enhancement in their doctor's professionalism ( z = 2.864, P = 0.004), 69.0% reporting a positive influence on relationship with their GP ( z = 2.943, P = 0.003) and 79.7% reporting an increase in perceived ability to manage their chronic health condition with the 'translated' letter (z = 4.601, P < 0.001). There was no effect on EQ‐5D depression/anxiety scores. Conclusion: Minimising the use of medical terminology in medical correspondence significantly improved patient understanding and perception of their ability to manage their chronic health condition. Although there was no impact on EQ‐5D depression/anxiety scores, overwhelming patient preference for the 'translated' letter indicates a need for minimisation of medical terminology in medical correspondence for patients with chronic health conditions.